Public and private art funding in Brazil - Durand, José Carlos Garcia (2000)
Tax incentives to fuel corporate sponsorship for the arts have been introduced in many countries, during the 80's and 90's. Brazil is one of them. To better understand symbolic, political and economic interests involved with such support, this article emphasizes both macro and micro perspectives. From a macro perspective, it examines the impact of neoliberalism on the Brazilian society, and also how economic and political life shape a climate appropriate to business sponsorship. From the micro perspective it analyses the pros and cons in the debate involving artists, public and private cultural managers, and other groups. Using Weberian categories, and avoiding naïve enthusiasm toward business in the arts, the article opposes the modern 'neoliberal privatization' of culture to the 'patrimonial privatization', as can historically be seen in the socially restricted, unaccountable and often low effective government performance in the area.